METHODOLOGY FOR APPLYING A DIGITAL PLATFORM IN THE PROFESSIONAL TRAINING OF QUALIFIED WORKERS IN THE MACHINE-BUILDING INDUSTRY (Innovative professional education, 2025)
The article examines the methodology for applying a digital platform in the professional training of qualified workers in the machine-building industry. It describes the modular structure of training, the integration of interactive tools, simulation modules, and adaptive learning. Key aspects of utilizing virtual laboratories, digital simulators, and educational process personalization algorithms are identified to enhance the competency level of learners and align the educational content with the requirements of modern manufacturing.
Keywords: digital platform, professional training, machine-building industry, interactive technologies, simulation modules, adaptive learning, virtual laboratories, education personalization